Sull'omissione del pronome clitico oggetto in italiano antico - Egerland, Verner (Verbum – Analecta Neolatina, 2002)
In conjoined structures in Modern Italian, clitic pronouns are to be repeated, even if exceptions from this rule are to some extent acceptable, as in lo leggo e rileggo. The Old Italian grammar appears to have been considerably more liberal on this point. In a 13th century text such as Il Libro de' Vizî e delle Virtundi, the omission of clitic pronouns in the second conjuct of a conjoined structure is highly frequent. This pronominal system, however, is not generally valid for the entire Old Italian period. Arguably, some 13th and 14th century authors cancel clitics in context where null objects cannot be recovered in Modern Italian. This indicates that some alternative recovery strategy was indeed available at an earlier stage of Italian.